ANALISIS KECERDASAN NATURALIS SISWA DALAM PEMBELAJARAN IPAS DI KELAS 4 SD 5 KANDANGMAS - Muhammad Thoha; Sri Utaminingsih; M. Syafruddin Kuryanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe the naturalist intelligence of students in grade 4 SD 5 Kandangmas. The method used in this research is descriptive qualitative. The informants of this research were the 4th grade students of SD 5 Kandangmas namely ALR, AR, DMZ, NAN, MAAA, KN, as the research sample using purposive sampling method. Collecting research data using observation, interviews, and documentation. The results of this study indicate that the naturalist intelligence of students in learning natural sciences in grade 4 SD 5 Kandangmas is quite good. This is shown from the findings of the researchers, namely, (a) many students like animals, (b) many students like plants, (c) Many students like outdoor activities and have concern for animals and plants, (d) Many students like activities related to nature, (e) Many students are interested in various activities outside the home and gardening.